ANALYSIS OF ESTROGEN DEFICIENCY ASSOCIATION WITH SALIVARY 25-HYDROXYVITAMIN D AND SALIVA FLOW RATE IN POSTMENOPAUSAL WOMEN WITH OSTEOPOROSIS - DARWIS, AIDA FADHILLA; SYAHPUTRA, ARMIA; HARAHAP, SEFTY A.; SUJATMIKO, PRASOJO; SYAH, MUHAMMAD KEYVIN; SITORUS, CINDY C. (International Journal of Applied Pharmaceutics, 2025)
Objective: This study analyzes the relationship between estrogen deficiency, salivary 25-hydroxyvitamin D, and salivary flow rates in postmenopausal women with osteoporosis. Methods: A cross-sectional study involved 52 patients with Osteoporosis at Orthopaedic Installation Putri Hijau Hospital as subjects by purposive random sampling. The inclusion criteria were participants who had menopause for at least two years, did not take (vitamin D supplements, antihypertensives, antihistamines, antidepressants, replacement estrogen hormone therapy, experience parathyroid hormone disorders, Sjogren's Syndrome, diabetes, obesity, and/or currently undergoing cancer therapy. Excluded those who vomited or were unable to sit. Saliva samples were collected using the spitting method and estrogen and 25-hydroxyvitamin D levels were calculated using an ELISA kit, and saliva flow rate using a measuring glass. The data were analyzed using the Spearman correlation test. Results: The mean value of salivary estrogen was 8 pg/ml, salivary 25-hydroxyvitamin D was 9.17 ng/dl, and salivary flow rate was 0.177 ml/minute. Based on the results of the Spearman correlation test between salivary estrogen and salivary 25-hydroxyvitamin D, it had a significant value (p<0.001) in the positive direction (r=0.925), and salivary estrogen and salivary flow rate had a significant value (p<0.001) in the positive direction (r=0.818). Conclusion: there is a relationship between salivary estrogen and salivary 25-hydroxyvitamin D and salivary flow rate, with a positive correlation and significant value, meaning that the lower the salivary estrogen, the lower the salivary 25-hydroxyvitamin D and salivary flow rate.